Haji Ramah Lansia Antara Kenyataan dan Tantangan Istitha'ah Kesehatan - Siregar, Alya Rahmayani; Sazali, Hasan (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Hajj is one of the pillars of Islam that must be carried out by Muslims who are physically, financially and mentally able. However, with the increasing elderly population among Hajj pilgrims, special health challenges arise, requiring special attention to ensure that their needs are optimally met during the Hajj pilgrimage. This research aims to investigate the reality of the elderly-friendly Hajj program and the challenges related to the health istitha'ah (physical and mental abilities) of elderly pilgrims during the Hajj pilgrimage. This research uses qualitative methods with a health istitha'ah case study. Data was collected by conducting in-depth interviews with elderly Hajj pilgrims, Hajj medical officers, and representatives from related institutions. Data was also collected through participant observation during the Hajj pilgrimage. Data analysis was carried out thematically to identify general patterns in the experiences and challenges faced by elderly Hajj pilgrims. The research results show that the elderly-friendly Hajj program has produced several initiatives aimed at increasing accessibility and comfort for elderly Hajj pilgrims, such as the placement of special tents. and more affordable medical facilities. However, significant challenges still exist, especially related to the availability and quality of health services, a lack of understanding of the special needs of the elderly, and the physical and mental readiness of the congregation itself. This research provides valuable insights for parties involved in organizing Hajj pilgrims, including health authorities and Hajj organizers, to improve elderly-friendly Hajj programs and ensure that the health and welfare needs of elderly Hajj pilgrims are properly met. The practical implications of this research are also discussed in the context of providing more inclusive and sustainable health services for the elderly population in the context of the Hajj.